2009
DOI: 10.4040/jkan.2009.39.6.878
|View full text |Cite
|
Sign up to set email alerts
|

New Nurse Turnover Intention and Influencing Factors

Abstract: Purpose:The study was done to identify turnover intention in new nurses according to characteristics of the nurses and other factors affecting turnover and to provide data to set up a strategy to reduce the turnover. Methods: Data were collected from 1,077 new nurses who had less than 12 months employment experience and worked in one of 188 hospitals. Eight research instruments were used. Data analysis was done using SPSS WIN 15.0 program. Results: Several factors influence new nurse turnover intention. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 11 publications
2
37
1
16
Order By: Relevance
“…It can be said that appropriate support and planning must be established to prevent burnout of psychological nurses from counseling, therapeutical activities, education that require high level expertise, frequent recurrence of patients, psychological emergencies such as suicide or violence, and occurrence of accidents [1] Emotional intelligence varied depending on general characteristics such as age, education career, and job satisfaction. As result of this study, emotional intelligence increased as career was longer in which this is identical to the research results by Han, Sohn & Kim [19] that good relationships and effective communication can take place with subjects due to increase of emotional intelligence by increase of age or career. Also, emotional intelligence increased with higher education in which this is identical to the research results by Kim et al [20].…”
Section: Discussionsupporting
confidence: 78%
“…It can be said that appropriate support and planning must be established to prevent burnout of psychological nurses from counseling, therapeutical activities, education that require high level expertise, frequent recurrence of patients, psychological emergencies such as suicide or violence, and occurrence of accidents [1] Emotional intelligence varied depending on general characteristics such as age, education career, and job satisfaction. As result of this study, emotional intelligence increased as career was longer in which this is identical to the research results by Han, Sohn & Kim [19] that good relationships and effective communication can take place with subjects due to increase of emotional intelligence by increase of age or career. Also, emotional intelligence increased with higher education in which this is identical to the research results by Kim et al [20].…”
Section: Discussionsupporting
confidence: 78%
“…한편 간호사의 이직의도와 관련된 선행연구를 분석해보면 주로 대 상들이 중소병원 간호단위의 간호사 [10], 종합병원 간호사 [11], 응급실 간호사 [19], 신규간호사 [20], 중환자실 간호사 [21] …”
Section: 소진이란 스트레스를 더 이상 감당하지 못할 때 나타나는 직무스트 레스 반응의 한 형태로 부정적인 자아개념 및unclassified
“…A growing body of literature reports that voluntary turnover rate is positively correlated with voluntary turnover intention and that a useful strategy for reducing turnover rate is to reduce clinical nurses' voluntary turnover intention. 7,8 Clinical nurses who reported high levels of voluntary turnover intention tended to have a weaker commitment to both the organization and nursing practice than those who reported no voluntary turnover intention, leading to actual turnover and inducing voluntary turnover intention among other clinical nurses. 2,6 Hence, studies related to nursing turnover have attempted to explore various factors influencing voluntary turnover intention among clinical nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes toward their organizations, specifically with regard to job embeddedness, organizational commitment, organizational citizenship behaviour and satisfaction with organizational rewards, have been reported to be factors influencing voluntary turnover intention among nurses. 7,9 Previous studies have reported that job embeddedness is negatively correlated with turnover intention and is also a significant predictor of nurse retention. [10][11][12] In addition, organizational commitment, organizational citizenship behaviour and satisfaction with rewards were also associated with lessening turnover intention among nurses.…”
Section: Introductionmentioning
confidence: 99%